A utilização de um jogo de tabuleiro como um recurso auxiliar no ensino da tabela periódica no 1° ano do ensino médio - Silva, Jayana de Oliveira (Brasil, 2022)
The teaching of exact sciences has many difficulties in its development. Many students have several difficulties in their learning because, in addition to finding the content difficult, they do not feel motivated to study them, because they claim that they will never use them in their practical lives. In this context, it is necessary to develop tools that can be used as an aid in the teaching and learning process and, thinking about it, we present here a game that has the purpose of facilitating the teaching-learning of the chemical elements present in the Periodic Table. This theme is important because it is very present in the life of the student, since everything that exists is constituted by chemical elements that are present in the Periodic table. In addition, this content is foreseen in the curricular proposal for the 1st. year of High School, making it fundamental to the knowledge that will be acquired in the discipline of Chemistry. The work that we present was thought from a didactic sequence structured in seven moments, which are: 1: Presentation of the content and the project to be applied; 2: Presentation of the history of the Periodic Table; 3: Explanation of the divisions of the periodic table; 4: Approach of Periodic Properties; 5: Content evaluation; 6: Application of the game; 7: Application of the game evaluation questionnaire. With the application of the game, we hope to contribute to a better understanding of the distribution of the chemical elements in the Periodic Table, and thus to be able to contribute with other teachers, from the use of a game as an alternative facilitator for the teaching of the Periodic table.